2020
DOI: 10.1177/0004867420965697
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline as adjunctive treatment for major depressive disorder: Pooled data from two randomized controlled trials

Abstract: Background: Randomized controlled clinical trials that have investigated minocycline as an adjunctive treatment for major depressive disorder have proved promising. Data from two studies were pooled to evaluate more definitively whether the addition of minocycline to standard treatment for major depressive disorder leads to an improvement of depressive symptoms when compared with placebo. Methods: Both studies were multi-site, double-blinded, placebo-controlled trials of minocycline 200 mg/day added to treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…More recently, Zazula et al. [ 50 ] pooled the data from two studies and reached similar conclusions. However, Husain et al.…”
Section: Antibiotics As Antidepressantsmentioning
confidence: 64%
See 1 more Smart Citation
“…More recently, Zazula et al. [ 50 ] pooled the data from two studies and reached similar conclusions. However, Husain et al.…”
Section: Antibiotics As Antidepressantsmentioning
confidence: 64%
“…In a subgroup of patients who had psychotic depression, Miyaoka et al also found efficacy when the antibiotic was administered as an adjunctive therapy [49]. More recently, Zazula et al [50] pooled the data from two studies and reached similar conclusions. However, Husain et al found no evidence of minocycline efficacy in bipolar depression [51].…”
Section: Antibiotics As Antidepressantsmentioning
confidence: 83%
“…As expected, PSE exerted pharmacological effects on sickness, anxiety, and depressive-like behaviors as well as inhibitory effect on microglial over-activation in hippocampal CA3 region ( Figures 5A–F ). Pooled data for two RCTs recently showed that minocycline, a specific microglial inhibitor, improved depressive symptoms and reduced the severity of anxiety in a total of 112 participants with major depressive disorders ( Zazula et al, 2021 ). However, there is concern about other risks of using minocycline to treat anxiety and depression because it is also an antibiotic ( Schmidt et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Infliximab, a TNF-α antagonist, inhibited TNF receptor (TNFR)/nuclear factor κB (NF-κB) signaling and depressive symptoms in MDD patients who were exposed to early life stress [218]. Minocycline is a tetracycline antibiotic that mediated neuroprotective effects and alleviated depressive symptoms by modulating CRP_and IL-6 [219][220][221]. Medications used to treat inflammatory conditions, such as psoriasis, (guselkumab [222] and ustekinumab [223]), rheumatoid arthritis (etanercept [224] and tocilizumab [225]), hidradenitis suppurativa (adalimumab [226]) also improved depressive symptoms in these patients.…”
Section: Inflammationmentioning
confidence: 99%